Callogenesis of Dayak Onion (Eleutherine palmifolia) Bulb in response of Picloram, 2,4-D, and Kinetin - Noor Aini Habibah; Ananda Lutfiah; Alin Liana; Woro Anindito Sri Tunjung; Meti Indrowati; Furzani Pa’ee (Biosaintifika: Journal of Biology & Biology Education, 2023)
Dayak onion contains bioactive compounds that are traditionally used for medicine. The production of bioactive compounds can be increased through callus culture. This study aims to analyze the effect of the combination of plant growth regulator on the growth of Dayak bulb callus. The design of this study used a completely randomized factorial design with 2 factors. The first factor is the concentration of auxin. While the second factor is the concentration of kinetin. The parameters observed include the percentage of callus, the time of callus formation, fresh weight, dry weight, and callus morphology. In this study, a callus growth curve was also made to determine the best harvest time. The results showed that highest callus fresh weight was obtained in the P3K1 treatment. The percentage of callus formation in the picloram + kinetin treatment was higher than in the 2,4-D + kinetin treatment. The time of callus formation occurred in the combination of picloram + kinetin faster than the 2.4-D + kinetin treatment. The callus color is diverse,  while the texture of the entire callus is compact. The best callus induction medium for Dayak onion bulbs is to use picloram 2-4 ppm + kinetin0.025-0.5 ppm. The results of this study provide optimal growth regulatory information for the induction of dayak onion callus that has never been reported before. This information can be the basis for the development of methods of production of bioactive compounds from dayak onions through callus culture.